2018
DOI: 10.3892/mmr.2018.8621
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol protects late endothelial progenitor cells from TNF-α-induced inflammatory damage by upregulating Kr�ppel-like factor-2

Abstract: Cardiovascular risk factors can negatively influence late endothelial progenitor cell (EPCs) number and functions, thus EPCs biology is a clinical implications for cardiovascular diseases. The present study aimed to investigate the potential protective effects of resveratrol (RES) on tumor necrosis factor (TNF)-α-induced inflammatory damage in late endothelial progenitor cells (EPCs) and to elucidate the underlying mechanisms. Late EPCs at passages 3–5 were pretreated with RES at a concentration of 20 µmol/l f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…The findings on IL-4 and IL-5 corroborate the Th1 to Th2 ratio findings as they are major effector cytokines secreted by Th2 (45). The anti-inflammatory activity of resveratrol [which was the most abundant stilbene in the HELENA study (12)] has previously been reflected by increased IL-4 in a retrospective study (46) and decreased TNF-α in an in vitro study (47), making the positive association with sVCAM-1 rather contradictory.…”
Section: Inflammation and Polyphenol Classessupporting
confidence: 71%
“…The findings on IL-4 and IL-5 corroborate the Th1 to Th2 ratio findings as they are major effector cytokines secreted by Th2 (45). The anti-inflammatory activity of resveratrol [which was the most abundant stilbene in the HELENA study (12)] has previously been reflected by increased IL-4 in a retrospective study (46) and decreased TNF-α in an in vitro study (47), making the positive association with sVCAM-1 rather contradictory.…”
Section: Inflammation and Polyphenol Classessupporting
confidence: 71%
“…However, neither resveratrol nor pyrimethamine was able to regulate the production of this cytokine significantly, despite the trend toward a slight decrease that we observed. Resveratrol has been considered a powerful anti-inflammatory compound that is expected to reduce the production of inflammatory cytokines, such as TNF-␣ and IL-1␤, in most of the cases examined by many researchers (44,45). However, it is noteworthy that a few studies reported that resveratrol could also regulate this cytokine in the opposite way.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammaging dampening Aged humans [93] Autophagy-mitochondria AMPK and Sirt1 activation Worm, mouse [99,100] Pro-inflammatory cytokine levels decrease Mouse, humans [95,98] Anti-inflammatory T cell increase T cells [112] Adhesion molecule repression Endothelial cells [115][116][117][118] Resveratrol Inflammation NF-κB inhibition Macrophages, microglia [111,121] Autophagy-mitochondria AMPK and Sirt1 activation Worm, mouse [125] Mitochondria mtROS production decrease Mouse [127] Adhesion molecule repression Vascular endothelial cells [129] SASP blockade Senescent cells [131] NF-κB and JNK inhibition Mouse [132] Memory T cell differentiation Mouse [136] Pro-inflammatory cytokine expression and immune cell infiltration blockade Mouse brain [137,146,147] Microglia activation inhibition Mouse brain [139] Metformin…”
Section: Discussionmentioning
confidence: 99%
“…Thus, resveratrol attenuates inflammation in human umbilical vein endothelial cells (HUVEC) cells by a mechanism that depends on the Sirt1 mediated activation of autophagy [116]. Resveratrol also decreases the levels of important adhesion molecules, such as ICAM-1, in TNF-α stimulated endothelial progenitor cells [117] and HUVEC cells [118].…”
Section: Resveratrolmentioning
confidence: 99%